Complex Medium-Chain Triglycerides Mitigate Porcine Epidemic Diarrhea Virus Infection in Piglets by Enhancing Anti-Inflammation, Antioxidation, and Intestinal Barrier Function - Tingting Hu; Yunhao Liu; Sihui Gao; Xiaonan Zhao; Huangzuo Cheng; Youjun Hu; Huaqiao Tang; Zhiwen Xu; Chunlin Fang (Viruses, 2025)
Porcine epidemic diarrhea (PED), a highly contagious enteric disease caused by the porcine epidemic diarrhea virus (PEDV), is characterized by vomiting, diarrhea, and dehydration, leading to high mortality in newborn piglets and significant economic losses in the swine industry. The shortage of effective PED vaccines emphasizes the need to explore potent natural compounds for therapeutic intervention. It has been shown that glycerol monolaurate (GML) effectively inhibits PEDV replication in vivo and in vitro. Further investigation is needed to assess whether complex medium-chain triglycerides (CMCTs), composed of glyceryl tricaprylate/caprate (GTCC) and GML, offer an efficient anti-PEDV activity. In this study, piglets were orally infected with PEDV and exhibited typical clinical signs, including diarrhea and vomiting, accompanied by intestinal inflammation, oxidative stress, and tissue damage. CMCTs were administered orally twice daily for one week. In vivo findings indicate that CMCT treatment alleviated clinical signs and prevented weight loss. It significantly increased serum immunoglobulins (IgG, IgM, and IgA) and intestinal mucosal sIgA and MUC-2 levels, while reducing pro-inflammatory cytokines (IL-1β, IL-6, TNF-α, and IL-17) and increasing antiviral interferons (IFN-α and IFN-γ), anti-inflammatory cytokines (IL-4 and IL-10), and IL-22. Antioxidant enzyme activities (T-AOC, SOD, GSH-Px, and CAT) were elevated, whereas oxidative stress markers (iNOS, NO, and MDA) were decreased. Expression of intestinal tight junction proteins claudin-1 and ZO-1 was restored. Moreover, CD4+ and CD8+ T cell populations increased, and the functions of regulatory T cells (Tregs) were restored. Gut microbiota analysis showed increased beneficial genera (Streptococcus and Ligilactobacillus) and decreased pathogenic Escherichia-Shigella. These results demonstrate that CMCTs mitigate PEDV infection by enhancing anti-inflammation, antioxidation, and intestinal barrier function, as well as modulating gut microbiota composition. This study improves the understanding of the pathogenesis of PEDV and highlights CMCTs as a promising therapeutic candidate for PED.